Sinkretisme dalam adat tradisi masyarakat Islam - Ros Aiza Mohd Mokhtar; Che Zarrina Sa‘ari (2016)
In the study of religion, syncretism has conveyed a controversial concept and become one of the issues being debated because it depicted “impurity” or “not authentic”. The term definitely has been widely used by Western scholars to elaborate the phenomenon of syncretism among ancient and Christian societies, but, at the same time it is also used in the context of the Muslim community, particularly in describing the practice of traditional culture in Malaysia and elsewhere that led to the rejection of traditional culture by the Muslim reformers. Therefore, this paper aims to describe the concept of syncretism as well as to analyze this concept from Islamic perspective in order to explain how it appeared in the context of traditional culture and how we could perceive or deal with it. In this study, library research is used for the purpose of collecting data. The data were then analyzed in descriptive and analytical way in order to explain the syncretism within traditional culture of the Muslim society. The study found that the image of “impurity” or “not authentic” brought about by syncretism within the traditional culture of Muslim society related to the mixing of Islam and pre-Islamic elements which are still in conflict with the principle of Tawhid. It is temporary and can be extinguished, while the traditional culture may be continued if the conflict no longer exists.